Detection of river flow slow-down through sensing system and quasi-real time imaging. (October 2021) - Lay-Ekuakille, Aimé; Ugwiri, Moise Avoci; Telesca, Vito; Velazquez, Ramiro; Passarella, Giuseppe; Maggi, Sabino
Abstract: Flow slow-down in rivers and artificial canals is a basic aspect to be monitored and kept strictly under control. Flow slow-downs can become a major concern in the event of extreme phenomena. The paper illustrates an advanced image processing method that uses particle tracking velocimetry in conjunction with a monadic approach to better characterize water flow in the presence of waste or debris that block normal water flow within a river. An high-speed camera installed beneath a bridge takes periodic images of the water flow. The measured water level and the images taken by the camera are sent to a central system in real-time. Results demonstrate the capability of the proposed method to accurately detect the presence of debris from the measured water flow. Highlights: Detecting water flow in channels by means of imaging using particle tracking velocimetry Retrieving detrital materials using robotic vision thanks to monadic approach Region of interest in river flow measurements Edge detection/contouring for trash materials in river